Skin Microbial Community Associated to Strawberry Disease in Farmed Rainbow Trout (Oncorhynchus mykiss Walbaum, 1792) - Alda Pardo; Alejandro Villasante; Jaime Romero (Microorganisms, 2024)
Aquaculture plays a crucial role in addressing the growing global demand for food. However, diseases associated with intensive aquaculture practices, especially those affecting the skin, can present significant challenges to both fish health and the industry as a whole. Strawberry disease (SD), also known as red-mark syndrome, is a persistent and non-lethal skin condition observed in Rainbow Trout (Oncorhynchus mykiss) in the United States and various European countries. SD is a nonlethal skin condition of an unclear etiology that affects rainbow trout reared in freshwater close to the harvest period. We used a RNA-based approach to examine active microbiota in the SD skin lesions and compared to non-injured skin. Our results, based on using 16S rRNA gene next-generation sequencing, showed that the skin microbiota was dominated by the phyla Firmicutes, Proteobacteria, and Actinobacteria. The comparisons of the skin microbiota between injured and non-injured samples showed differences in the alpha diversity (Fisher index) and beta diversity metrics (ANOSIM). At the genus level, both Pseudomonas and Candidatus Midichloria were highlighted as the most abundant taxa detected in samples obtained from fish affected with strawberry diseases. In contrast, the most abundant taxa in non-injured skin were Escherichia-Shigella, Streptococcus, and Pseudoalteromonas. In conclusion, our study on SD revealed distinct differences in the microbiota composition between skin lesions and non-injured skin. This is the first description of microbiota associated with SD-injured skin samples using an RNA approach.